ANALYSIS AND ASSESSMENT OF THE IMPACT OF DISASTERS AND ACCIDENTS ON THE FUNCTIONING OF RURAL AREAS IN BULGARIA - Kamen PETROV; Nikolay TZONKOV; Tzvetelina BERBEROVA-VALCHEVA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This article is devoted to analyzing and assessing the impact of disasters and accidents on the conditions for the socio-economic and demographic development of rural areas in Bulgaria. The topicality of the topic is caused by the necessity of the new conditions of globalization to overcome regional and local risks related to the population's way of life. To a large extent, the processes of urbanization and the relocation of the population in urban areas lead to the creation of threats to its security, mainly by disrupting the reliability of the functioning of the natural-ecological and socio-economic systems. Therefore, rural areas and their potential for security and regional development must be strengthened. In this regard, it is important to create the necessary basic conditions for the life and development of the population - minimum infrastructure, taking measures to reduce natural and environmental risks through a system encompassing activities and facilities for monitoring, maintaining, and cleaning riverbeds and forests in sparsely populated areas in Bulgaria.